Primary structure of lymphocyte function-associated antigen 3 (LFA-3). The ligand of the T lymphocyte CD2 glycoprotein. - Wallner, B; Frey, A; Tizard, R; Mattaliano, R; Hession, C; Sanders, M; Dustin, M; Springer, T (1987)
We have isolated the cDNA for human lymphocyte function-associated antigen 3 (LFA-3), the ligand of the T lymphocyte CD2 molecule. The identity of the clones was established by comparison of the deduced amino acid sequence to the LFA-3 NH2-terminal and tryptic peptide sequences. The cDNA defines a mature protein of 222 amino acids that structurally resembles typical membrane-anchored proteins. An extracellular domain with six N-linked glycosylation sites is followed by a hydrophobic putative transmembrane region and a short cytoplasmic domain. The mature glycoprotein is estimated to be 44-68% carbohydrate. Southern blots of human genomic DNA indicate that only one gene codes for human LFA-3. Northern blot analysis demonstrates that the LFA-3 mRNA of 1.3 kb is widely distributed in human tissues and cell lines.